Biopharmaceutical evaluation of new semi-solid preparation with thiotriazoline and chloramphenicol - Zubachyk, Volodymyr; Holeyko, Marta; Vashchenko, Oksana (Journal of Medical Science, 2014)
Introduction. Periodontitis numbers among the most widespread diseases. The prevalence of the periodontal inflammation does not tend to decrease, but long-term history of the disease, the complexity in treatment significantly reduce the quality of life in patients, cause the tooth loss. An important principle for the treatment of mentioned disorder is use of drug products in the lesion location. The preference is given to semi-solid preparations with a polyvalent pharmacological action which can eliminate the causative agents and affect the different elements in the pathogenesis. Aim. Aim of the study was to evaluate the influence of excipients, including the base-forming agents, on the thiotriazoline release from semi-solid preparation and based on the results of investigations to develop the composition of a new drug product for treatment of periodontal inflammation. Material and methods. Thiotriazoline and chloramphenicol were selected as active pharmaceutical ingredients for the development of semi-solid preparation. Methylcellulose, carboxymethylcellulose sodium and polymethylsiloxane (base-forming agents); glycerol and propylene glycol (plasticizers); methylparaben and propylparaben (preservative agents); peppermint oil (flavouring agent) were also used in the investigations on the pharmaceutical development. In order to select an optimal composition of the base for dental semi-solid preparation with thiotriazoline and chloramphenicol, six samples with different content were prepared. The appearance of samples was evaluated visually. Measurement of pH value was performed using pH-Meter-240 CORNING. Thiotriazoline release from the test samples was studied in vitro by agar diffusion method. Results and conclusions. The results of investigations showed that excipients largely affected thiotriazoline release from the drug product. According to the results of physical, physical-chemical and biopharmaceutical investigations the following excipients were chosen for the development of dental semi-solid preparation: methylcellulose (base-forming agent), glycerol (plasticizer), methylparaben and propylparaben (preservative agents), peppermint oil (flavouring agent with antiseptic action). Developed preparation is homogeneous mass with a thick consistency, white color and pleasant fresh smell. The drug product is characterized by stable physical-chemical and rheological properties, and has a neutral pH.